Republic of Latvia : Stand-By Arrangement; Interim Review Under the Emergency Financing Mechanism. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the Stand-By Arrangement-Interim Review under the Emergency Financing Mechanism for the Republic of Latvia. Financial market pressures in Latvia have eased somewhat since program approval: deposit outflows have slowed and the exchange rate has moved off the weaker end of its band. However, new risks are emerging. The recession has intensified, facilitating external adjustment but lowering tax revenues. Though sizable, fiscal policy adjustment has fallen short of commitments in the program, owing to weaknesses in implementation and difficulties in reducing local government expenditure.